2002
DOI: 10.1051/0004-6361:20021504
|View full text |Cite
|
Sign up to set email alerts
|

Star-forming complexes and the spiral structure of our Galaxy

Abstract: Abstract.We have carried out a multiwavelength study of the plane of our Galaxy in order to establish a star-forming-complex catalogue which is as complete as possible. Features observed include Hα, H109α, CO, the radio continuum and absorption lines. For each complex we have determined the position, the systemic velocity, the kinematic distance and, when possible, the stellar distance and the corresponding uncertainties. All of these parameters were determined as homogeneously as possible, in particular all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
599
8
26

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(691 citation statements)
references
References 81 publications
58
599
8
26
Order By: Relevance
“…2 is at a galactocentric distance where the spiral pattern of the Galaxy is not yet clearly visible (molecular ring, see e.g. Russeil 2003). The latter argument is also supported in Fux (1999), where it is shown that the existence of a bar in our Galaxy does not significantly affect the dynamics outside the molecular ring.…”
Section: Spatial Distribution Of the Maserssupporting
confidence: 60%
See 1 more Smart Citation
“…2 is at a galactocentric distance where the spiral pattern of the Galaxy is not yet clearly visible (molecular ring, see e.g. Russeil 2003). The latter argument is also supported in Fux (1999), where it is shown that the existence of a bar in our Galaxy does not significantly affect the dynamics outside the molecular ring.…”
Section: Spatial Distribution Of the Maserssupporting
confidence: 60%
“…In the case of galactic sources, kinematic distances from spectral line observations are becoming more accurate thanks to improved modelling of the Galactic rotation curve (e.g. Brand & Blitz 1993 as well as Russeil 2003). The difficulty resides in the discrimination between near-and farheliocentric distances for all sources on orbits internal to the Solar orbit around the Galactic Centre.…”
Section: Modelling the Maser Distribution And Luminosity Functionmentioning
confidence: 99%
“…The heliocentric photometric distance d was calculated adopting the calibration of the absolute magnitude M V as a function of the spectral type and luminosity class given by Russeil (2003). The error in distance was estimated to be…”
Section: Reddening Correction and Distance Determinationmentioning
confidence: 99%
“…the review by Vallée 2013). The main achievement of this purely spiral model is that it can explain the distribution of HII regions in the Galactic disk (Russeil 2003). This model became more physical after incorporation of the bar into it (Englmaier & Gerhard 1999).…”
Section: Introductionmentioning
confidence: 99%